2010
DOI: 10.1016/j.bbamcr.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptors amplify dopamine D1 receptor signaling at presynaptic sites in the prelimbic cortex

Abstract: Sigma-1 receptors are highly expressed in the brain. The downstream signaling mechanisms associated with the sigma-1 receptor activation have been shown to involve the activation of protein kinase C (PKC), the control of Ca(2) homoeostasis and the regulation of voltage- and ligand-gated ion channels. But few studies examined the regulatory effect of sigma-1 receptors on metabotropic receptor signaling. The present paper studied the regulatory effect of sigma-1 receptors on the signaling of dopamine D1 receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…NDHEA sulfate, a sigma-1 receptor agonist, inhibits persistent sodium currents in the rat medial prefrontal cortex via the G i protein and the PKC signaling pathways [36]. The sigma-1 receptor ligand PRE-084 amplifies dopamine D1 receptor signaling in the prelimbic cortex [37]. G-protein blockade or activation using G i/o and G s inhibitors did not alter the (+)-SKF 10047 -induced inhibition of Na V 1.2 channel currents.…”
Section: Discussionmentioning
confidence: 91%
“…NDHEA sulfate, a sigma-1 receptor agonist, inhibits persistent sodium currents in the rat medial prefrontal cortex via the G i protein and the PKC signaling pathways [36]. The sigma-1 receptor ligand PRE-084 amplifies dopamine D1 receptor signaling in the prelimbic cortex [37]. G-protein blockade or activation using G i/o and G s inhibitors did not alter the (+)-SKF 10047 -induced inhibition of Na V 1.2 channel currents.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have demonstrated an influence of membrane lipids on DAT trafficking (Foster et al, 2008) and transport capacity (Adkins et al, 2007). More recently, Hong and Amara (2010) have suggested on the basis of substituted cysteine accessibility methods that a cholesterol-rich membrane environment shifts the DAT conformational equilibrium toward a Fu et al (2010) indicates that the R agonist, PRE-084, which had no effects of its own, amplified the effects of the D 1 R partial agonist, SKF 38393. In addition, Navarro et al (2010) showed evidence supporting heteromerization of and dopamine D 1 receptors and a potentiation of D 1 R-mediated adenylyl cyclase activation by actions at Rs.…”
Section: Discussionmentioning
confidence: 99%
“…Since ADAM10 function is induced by free Ca 2+ in cell (Sanderson et al, 2005;Horiuchi et al, 2007), such inhibition could thus inhibit ADAM10-dependent BTC shedding. On the other hand, although sigma-1 receptor agonists could activate PKC (Fu et al, 2010;Yoon et al, 2010) which can in turn activate ADAM17-dependent shedding (Zheng et al, 2002(Zheng et al, , 2004Sahin et al, 2004), such an effect might be covered by the Figure 3. ADAM10-depedent BTC shedding is more sensitive to membrane lipid change while ADAM17-dependent HB-EGF shedding was not.…”
Section: Discussionmentioning
confidence: 99%